Testing The Model Of Success Experience In Converting Into Islamic Banks In Libya Structural Equation Modeling - Muhammad Ridhwan. Aziz; Marai.A.D.Abdalla (American Research Institute For Policy Development, 2024)
Journal of Islamic Banking and Finance, Vol. 3(2), December 2015